Pengaruh Motivasi Belajar dan Lingkungan Belajar Siswa terhadap Hasil Belajar Siswa Mata Pelajaran IPS Kelas VII dan VIII SMP Maulana Pagayaman - Komang Isma Pramitha; Made Ary Meitriana (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to examine and analyze the influence of learning motivation and learning environment on student learning outcomes in Social Sciences (IPS) in grades VII and VIII of Maulana Pegayaman Middle School. This study was conducted using a quantitative research method with a causal approach. The data analysis technique used was multiple linear regression to determine the extent to which the independent variables, namely learning motivation and learning environment, influence the dependent variable, namely student learning outcomes. The population in this study were all students in grades VII and VIII of Maulana Pegayaman Middle School with a total of 86 respondents. The sample was determined using a saturated sampling technique, so that the entire population was used as the research sample. Data collection was obtained through the distribution of questionnaires whose validity and reliability had been previously tested to ensure the quality of the measurement instruments. The results of the data analysis showed several important findings. (1) Partially, learning motivation has a positive and significant effect on the social studies learning outcomes of students in grades VII and VIII of Maulana Pegayaman Middle School. (2) Partially, the learning environment has a positive and significant effect on the social studies learning outcomes of students in grades VII and VIII of Maulana Pegayaman Middle School; (3) Simultaneously, learning motivation and the environment have a significant influence on the social studies learning outcomes of class VII and VIII students at Maulana Pegayaman Middle School.